The Effect of Using Illustrated Folklore Series in Reading Comperhension Ability of The Second Grade Students’ at SMP Negeri 24 Kota Jambi in Academic Year 2018 - Kartika Dewi (Jurnal Sains Sosio Humaniora, 2018)
This study was a discussion about ability reading comprehension and the purpose of the study is to find out the application of Folklore series illustrate in improving the ability of students; reading comprehension of the Second Grade Students at SMP 24 Kota Jambi in Academic Year 2018. The research is designed by using pre and post-test design. This research design is chosen to refer to its superiority in controlling for extraneous factors that may influence the outcome though random assignment procedure. The pre-test result showed that the mean score of data was 53.66. From the pre-test result, it could be seen the lowest score was 36.66 and the highest score was 70. The post-test result in this group shown that the mean score of the post-test result is 74.32 test result with the lower score was 43.33 and the highest score was 90.The analysis the mean score of students; reading comprehension by using illustrated Folklore it effect of using ore Series was higher than mean score of students; reading comprehension not using illustrated Folklore Series. It means the effect of using comprehension at SMP Negeri 24 Kota Jambi was accepted.